Random Telegraph Signal Noise in Advanced High Performance and Memory Devices - Claeys, C.; Andrade, M. G. C. de [UNESP]; Chai, Z.; Fang, W.; Govoreanu, B.; Kaczer, B.; Zhang, W.; Simoen, E.; IEEE (Ieee, 2016)
Random Telegraph Signal noise has been extensively studied for more than 30 years and gained high interest in recent years due to its importance for scaled down technologies. This review will demonstrate the power of RTS for single defect characterization. Present understanding of the device physics and evolutions in RTS characterization are highlighted. Special attention is given to RTS in memory devices such as DRAMS, ReRAM, planar (2D) and vertical (3D) flash.
Keywords: random telegraph signal; time lag plot; ReRAMs; low frequency noise; interface traps; UTBB SOI; oxide traps